2020
DOI: 10.3390/ijms21218122
|View full text |Cite
|
Sign up to set email alerts
|

Desmin Interacts Directly with Mitochondria

Abstract: Desmin intermediate filaments (IFs) play an important role in maintaining the structural and functional integrity of muscle cells. They connect contractile myofibrils to plasma membrane, nuclei, and mitochondria. Disturbance of their network due to desmin mutations or deficiency leads to an infringement of myofibril organization and to a deterioration of mitochondrial distribution, morphology, and functions. The nature of the interaction of desmin IFs with mitochondria is not clear. To elucidate the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
1
31
0
2
Order By: Relevance
“…Vice versa, static anchors such as the microtubule binding protein SNPH actively stop mitochondria at ATP-deficient sites 27 . Also NFs, desmin and vimentin all bind to mitochondria regulating their dynamics and distributions 9,26,32,33,45,46 . But also IF-associated proteins such as plectin 1b are able to connect the IF-network to mitochondria 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vice versa, static anchors such as the microtubule binding protein SNPH actively stop mitochondria at ATP-deficient sites 27 . Also NFs, desmin and vimentin all bind to mitochondria regulating their dynamics and distributions 9,26,32,33,45,46 . But also IF-associated proteins such as plectin 1b are able to connect the IF-network to mitochondria 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial quality control, membrane potential, organization and function are all impaired upon loss of IFs [6][7][8] . It has also been shown that mutations in IFs affect mitochondrial size, density and respiratory function [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Η δεμσίνη με την αΒ-κρυσταλλίνη συνεντοπίζονται και στις περιοχές συσχέτισης του ενδοπλασματικού δικτύου με τα μιτοχόνδρια, τα MAMs, όπου αλληλεπιδρούν με τη VDAC, τη Mic60 (ή mitofilin), το κύριο συστατικό του MICOS συμπλόκου (mitochondrial contact site and cristae organizing system) και την ATP συνθετάση, συμβάλλοντας στη διατήρηση της μορφολογίας και της σωστής λειτουργίας των μιτοχονδρίων . Μάλιστα, πρόσφατα δείχθηκε ότι η δεσμίνη προσδένεται άμμεσα με τα μιτοχόνδρια μέσω της αμινο-τελικής περιοχής της (Dayal et al, 2020). Ο σπουδαίος ρόλος της δεσμίνης στη διασφάλιση της ομοιόστασης των μιτοχονδρίων, φαίνεται ξεκάθαρα από το πειραματικό μοντέλο ποντικού με έλλειψη δεσμίνης, το οποίο παρουσιάζει εκτεταμένες μιτοχονδριακές βλάβες μεταξύ άλλων, όπως θα συζητηθεί παρακάτω, αλλά και από το γεγονός ότι τα μιτοχόνδρια είναι από τα πρώτα οργανίδια που προσβάλλονται τόσο κατά την απουσία της δεσμίνης, όσο και σε περιπτώσεις μεταλλάξεων των σχετιζόμενων με τη δεσμίνη πρωτεϊνών (Milner et al, 1996, Milner et al, 2000Maloyan et al, 2005;Galata et al, 2018;Winter et al, 2015).…”
Section: H υποκυτταρική κατανομή της δεσμίνης και ο ρόλος της στα μυοκαρδιοκύτταραunclassified
“…. Μάλιστα, αρκετά πρόσφατα δείχθηκε ότι η δεσμίνη αλληλεπιδρά άμεσα με τα μιτοχόνδρια μέσω του αμινο-τελικού της άκρου (Dayal et al, 2020). Επομένως, προτείνεται ότι η διατάραξη της αλληλεπίδρασης του δικτύου των ινιδίων της δεσμίνης με τα μιτοχόνδρια, επηρεάζει τη σωστή τοπολογία τους, η οποία με τη σειρά της επηρεάζει και τη λειτουργία τους.…”
Section: η απουσία της δεσμίνης επηρεάζει τη λειτουργία των μιτοχονδρίωνunclassified